2004
DOI: 10.1093/hmg/ddh145
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor-acetylhydrolase and PAF-receptor gene haplotypes in relation to future cardiovascular event in patients with coronary artery disease

Abstract: Oxidation of low density lipoproteins is an initial step of atherogenesis that generates pro-inflammatory phospholipids, including platelet-activating factor (PAF) and its analogs. PAF is degraded by PAF-acetylhydrolase (PAF-AH), a circulating enzyme having both pro- and anti-inflammatory activities. PAF-AH activity has been postulated to be a risk factor for coronary artery disease (CAD); however, whether PAF-AH has a causal role or is simply a marker of risk is unclear. The aim of this study was to relate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 36 publications
8
67
1
3
Order By: Relevance
“…In agreement with our study, Ninio e et al, 22 Abuzeid AM et al, 23 and ling lC et al, 24 reported that the homozygous (tt) and heterozygous (Ct) forms of 379V polymorphism were less frequent in MI patients than in controls, suggesting that this allele might be protective against the development of CAd while A379 variant was more prevalent among patients.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study, Ninio e et al, 22 Abuzeid AM et al, 23 and ling lC et al, 24 reported that the homozygous (tt) and heterozygous (Ct) forms of 379V polymorphism were less frequent in MI patients than in controls, suggesting that this allele might be protective against the development of CAd while A379 variant was more prevalent among patients.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, the 2 top SNPs for Lp-PLA2 activity and RPW are in the PLA2G7 gene and were significantly associated with Lp-PLA2 activity in the Framingham Offspring cohort and in previous studies. 35 In our exploratory analyses, we were not able to show strong evidence for mendelian randomization for the inflammatory biomarkers examined (including Lp-PLA2). We acknowledge that many of the conditions required to infer causality under mendelian randomization were not met in the present project.…”
Section: Snps Biomarkers and Tonometry Variablesmentioning
confidence: 71%
“…For eight additional genes (CCR5, CNDP1, HNF4A, LTA, PON2, GCGR, INPPL1, PLA2G7), polymorphisms were selected according to reported associations with phenotypes relevant for diabetic nephropathy (13)(14)(15)(16)(17)(18)(19)(20). We also examined 94 SNP markers (genomic control markers) in nongenic regions spaced throughout the genome to control for possible stratification within each population (21,22).…”
Section: Methodsmentioning
confidence: 99%